3D TUDE MOVIE SERIES “BELAJAR MATEMATIKA BERSAMA TUDE” - I Wayan Pandu Wibawa S; Padma Nyoman Crisnapati; Made Windu Antara Kesiman; I Gede Mahendra Darmawiguna (Universitas Pendidikan Ganesha, 2013)
Originally cartoon is a two-dimensional film, but as the development time and technology, cartoons developed a threedimensional cartoon. Along with the advancement of technology development is very rapid progress animated films. With the development of the animated films are not only attractive to children’s but can be enjoyed by all the people. In the cartoon could insert lessons that can educate or to provide knowledge for the audience, although the cartoon animation can also be used as a means to promote education or media of education. People watching cartoon films also learn from what is viewed on the cartoon, for example, can be embedded the value of humanity in the cartoon story teaches people to do good attitude. Beside that can interlining Mathematics Education and pasting the exercise directly with the solution. This lesson is often acquired through books, but in the book it is difficult to imagine the lesson so that the movement of animation and cartoon character that attracts people become more easy to imagine and not bored to watch it. So besides getting entertained audiences can also add to the knowledge of the cartoons. Therefore, in this thesis author tries to make the animation work of 3 dimensional using Blender 2.65 software with several stages of animation that is pre-production, production, and post production